Kajian Kapasitas Ruas Jalan Lenteng Agung Raya Setelah Adanya Fly Over U-Turn Lenteng Agung - Pahrul Rodji, Achmad; Sihombing, Sahat Martua; Mumpuni, Desni Citra (Jurnal Sipil Krisna, 2023)
Congestion on Jalan Lenteng Agung Raya, South Jakarta is a fairly frequent occurrence, such as in the morning when people start leaving for their respective activities and also in the afternoon when they return from their activities. Another cause of congestion is the existence of a U-Turn at railroad crossings that are parallel to the road, so that when the train is passing, the vehicle will automatically stop to queue and wait for the train to finish crossing and be stopped by the occurrence of high side obstacles along the road. Lenteng Agung Raya. That way, the government plans infrastructure development in the hope of reducing the congestion problem, namely the U- Turn flyover. The flyover is expected to reduce congestion. The construction of the Lenteng Agung U-Turn Flyover caused an increase in traffic volume. This condition is analyzed by calculating the volume and capacity of the road per lane, the free flow speed and the degree of saturation, as well as determining the category of road service level. Before the flyover, Jalan Lenteng Agung was traversed by vehicles with a daily traffic volume of 2263 smp/hour per lane, vehicle travel speed of 14.4 km/hour. Q/C Ratio 0.52, including service level category C, where the flow is stable, but the speed and movement of the vehicle controlled by the driver is limited in choosing the speed. After there is an overpass, the daily traffic volume is 2466 smp/hour per lane, the vehicle travel speed is 25.71 km/hour. Q/C Ratio 0.58 is in service level category C where the flow is stable, but the speed and motion of the vehicle controlled by the driver is limited in choosing the speed. The increase in traffic volume and the increase in the speed of vehicle travel that occurs is thought to be due to a change in the reversal crossing which originally passed the railroad tracks so that long queues of vehicles on Jalan Lenteng Agung have been replaced by flyovers.